(untitled) (Architecture Image Studies, 2026)
Medan City, as one of Indonesia’s economic and trade centers, has great potential for developing the MICE sector. However, MICE development in this city still faces various challenges, such as low awareness of sustainability, limited trained human resources, and suboptimal collaboration among stakeholders. This study aims to analyze the forms and characteristics of incremental innovation in the development of MICE destinations in Medan. This study uses qualitative research methods. The data collection techniques used in this study are semi-structured interviews, observation, group analysis, and focus group discussions (FGD). Data analysis will follow a systematic thematic analysis approach. The results of the study show that the transformation towards sustainable MICE tourism in Medan City takes place through incremental innovation that emphasizes gradual improvements such as digitization, the use of local products, and energy efficiency. This approach is considered most appropriate for local resource capacities and effective in building a culture of sustainable innovation. The integration of ESG principles strengthens environmental, social, and governance aspects through environmentally friendly practices, MSME empowerment, and cross-sector collaboration. The application of the Pentahelix concept forms the basis for inclusive and adaptive collaborative governance. In the future, policy support such as the formulation of Green MICE Guidelines, the provision of incentives, and the establishment of an ESG Forum are expected to make Medan a national and international sustainable MICE destination, while also supporting the achievement of SDGs 8, 12, and 17.